Ocular Tremor in Parkinson’s Disease: Discussion, Debate, and Controversy - Kaski, Diego; Bronstein, Adolfo M. (Frontiers in Neurology, 2017)
The identification of ocular tremor in a small cohort of patients with Parkinson’s disease (PD) had lay somewhat dormant until the recent report of a pervasive ocular tremor as a universal finding in a large PD cohort, that was however generally absent from a cohort of aged-matched healthy subjects. The reported tremor had frequency characteristics similar to those of PD limb tremor, but the amplitude and frequency of the tremor did not correlate with clinical tremor ratings. Much controversy ensued as to the origin of such a tremor, and specifically as to whether a pervasive ocular tremor was a fundamental feature of PD, or rather a compensatory eye oscillation secondary to a transmitted head tremor, and thus a measure of a normal vestibulo-ocular reflex. In this mini review we summarise some of the evidence for and against the case for a pervasive ocular tremor in PD, and suggest future experiments that may help resolve these conflicting opinions.